Effectiveness of pulse dose methyl prednisolone in management of COVID 19: A systematic review and meta-analysis of observational studies. - Rashmi Ranjan Mohanty; Biswa Mohan Padhy; Bikash Ranjan Meher (Frontiers Media S.A., 2022)
Purpose: Till date, only systemic corticosteroids have demonstrated definite mortality benefit in management of COVID 19 in various studies. Still certain questions regarding the appropriate dose, duration and timing of corticosteroids remain unanswered. For this reason, the study was planned to determine the efficacy and safety of the pulse dose methyl prednisolone in management of COVID 19 from the publicly available evidence. Methods: PubMed, the Cochrane library, ClinicalTrials.gov and medRxiv were searched for articles reporting the use of pulse dose methyl prednisolone in COVID 19 from inception till 31st May, 2021. Odds ratios (ORs) were calculated for estimation of pooled effect by using random effect model and heterogeneity was checked by using I2 statistics. Results: Twelve studies (11 observational and 1 RCT) were included in the systematic review. A total of 3110 patients from 9 studies were included in the meta-analysis. Though the use of pulse dose methyl prednisolone demonstrated statistically significant mortality benefit in comparison to usual care (OR=0.71, 95% CI: 0.51 to 0.97, [P=0.03]), (I2= 21%) with calculated Number needed to treat (NNT) of 23.5, there was no statistically significant difference between the use of pulse dose and low dose corticosteroid (OR=0.66, 95% CI: 0.44 to 1.01, [(P=0.05]), (I2= 25%) and the NNT is 23.5. Incidence of adverse events were similar across all the groups. The grade of evidence for primary outcome was of moderate certainty. Conclusion: This meta-analysis concurs with the previous reports regarding the use of corticosteroid in COVID 19 in comparison to usual care. However, for both the primary and secondary outcome, the study did not find any statistically significant difference between the use of pulse dose methyl prednisolone and low dose corticosteroid to treat COVID 19 patients